Does the Healthy China 2030 Policy Improve People’s Health? Empirical Evidence Based on the Difference-in-Differences Approach - Ning C; Pei H; Huang Y; Li S; Shao Y (Risk Management and Healthcare Policy, 2024)
Chuanlin Ning,1 Huacheng Pei,2 Youjia Huang,1 Sichen Li,1 Yiling Shao1 1School of Media and Communication, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 2School of Finance, Shanghai University of Finance and Economics, Shanghai, People’s Republic of ChinaCorrespondence: Yiling Shao, School of Media and Communication, Shanghai Jiao Tong University, No. 800, Dongchuan Road, Minhang District, Shanghai, 200240, People’s Republic of China, Email sylh1996@sjtu.edu.cnBackground: The Healthy China 2030 (HC2030) policy is currently recognized as China’s most significant and influential national health policy. However, despite its implementation in 2016, the policy’s impact has yet to be comprehensively evaluated, particularly in relation to its effectiveness in enhancing population health and promoting public health equity.Methods: We utilized the Difference-in-Differences (DiD) method to evaluate the impact of the HC2030. Our analysis utilized a panel dataset derived from five longitudinal surveys conducted by the China Family Panel Studies (CFPS).Results: The implementation of HC2030 has improved the overall health status of residents, particularly in urban areas and the western and eastern regions. Mechanistic analysis has further unveiled that the policy’s beneficial impact on health outcomes is attributed to a rise in physical activity frequency and the betterment of mental health. Additionally, female, married, and medically insured individuals have demonstrated a significant positive impact of the policy on their health outcomes.Conclusion: Although the HC2030 appears to have effectively improved overall population health, it needs to promote equity in public health adequately. The study suggests adjustments are needed to address the unequal distribution of health outcomes between urban and rural areas and among different regions.Keywords: health China 2030, health policy, policy evaluation, health equity, health communication, public health